2015
DOI: 10.3109/02713683.2015.1050743
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety and Acceptability of Orthokeratology on Slowing Axial Elongation in Myopic Children by Meta-Analysis

Abstract: Orthokeratology has significantly greater efficacy in controlling axial elongation in children compared to Spectacle correction. The safety and acceptability results are good, and there appears to be a greater myopia control effect in Chinese children compared to Caucasians, and in those with higher initial myopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
74
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 32 publications
5
74
1
2
Order By: Relevance
“…Orthokeratology and low‐dose (0.01%) atropine were considered to be more efficacious for slowing childhood myopia progression than single‐vision distance spectacles by most respondents. In a recent meta‐analysis, combining data from three randomised controlled trials and six cohort studies, orthokeratology was reported to significantly reduce axial elongation relative to a control (single‐vision distance) intervention . While this technique shows promise as an intervention for reducing childhood myopia progression, there are several important limitations to the existing research evidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Orthokeratology and low‐dose (0.01%) atropine were considered to be more efficacious for slowing childhood myopia progression than single‐vision distance spectacles by most respondents. In a recent meta‐analysis, combining data from three randomised controlled trials and six cohort studies, orthokeratology was reported to significantly reduce axial elongation relative to a control (single‐vision distance) intervention . While this technique shows promise as an intervention for reducing childhood myopia progression, there are several important limitations to the existing research evidence.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, combining data from three randomised controlled trials and six cohort studies, orthokeratology was reported to significantly reduce axial elongation relative to a control (single-vision distance) intervention. 24 While this technique shows promise as an intervention for reducing childhood myopia progression, there are several important limitations to the existing research evidence. To date, most studies have been single-site trials, involving relatively small numbers of participants (n = 40-50 per group) of predominantly Asian ethnicity, and have evaluated the efficacy of orthokeratology over a two-year period; there is a dearth of longer-term prospective data to inform the longevity of effects.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many groups have reported the efficacy of various treatments in reducing progression of myopia, such as atropine eyedrops[8,9], orthokeratology[10,11], and specialized contact lens[12]. However, all these treatment options may suffer potentially severe side effects [8,13], and thus may raise challenges in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…S. Li и соавт. [34] в 2016 г. в своем метаанализе на основе 3 рандомизированных контролируемых исследований (РКИ) и 6 когортных исследований показали, что средняя разница удлинения ПЗО глаза между группой ночных линз и группой контроля через 6 мес, 1 год, 1,5 и 2 года составила 0,13, 0,19, 0,23 и 0,27 мм (р < 0,01) соответственно. J. Si и соавт.…”
unclassified